Singiran: Pendekatan Sosio-kultural Pembelajaran Islam dalam Pesantren dan Masyarakat NU - Kholid Mawardi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Sosio-cultural approach in Islamic learning becomes preference of pesantren and society NU as consequence from their moderate and tolerant religious view. This approach based on their appreciation to local tradition and strives the balance among former tradition (local tradition) with the new tradition (Islam). Therefore, cultural change process occurs well and smooth. One of its approaches is singiran. Singiran is Java’s poems comprising about tauhid, fikih, and tasawuf that adapted from kitab kuning texts. Singiran is not detached from sacred religious value (from traditionalist Islam perspective) because written in Arab Pegon letter, and do not confusing its audience because composed in Javanese.